White Shrimp (Litopenaeus vannamei) Production on Different Rearing Densities in Biocrete Pond - Budiardi, T.; Muzaki, A.; Utomo, N.B.P. (Jurnal Akuakultur Indonesia, 2005)
Study on white shrimp (Litopenaeus vannamei) production in biocrete pond in different density was performed at PT. Bimasena Segara, Citarate, Sukabumi, West Java. Six ponds were used and devided into 2 groups based the density levels, i.e., 72-73 shrimp/m2 and 93-105 shrimp/m2.  Experiment was done for 100 days, including pond preparation.  The results of study showed that mean weight of shrimp reared in biocrete pond was ranged from 9.64 to 12.34 gram, survival rate 26.97-99.58%, productivity 3,078-8,340.9 kg/ha, feed quantity 2,084.5-2,870.4 kg and FCR 1.19-2.60.  Ponds with lower rearing density had lower (P